Influence of family on secondary school students’ aspirations for entrepreneurial careers in Ilorin Metropolis, Nigeria (Journal of Educational Management, 2014)
The study investigated the influence of family on secondary school students' aspirations for entrepreneurial careers in IIorin metropolis, Nigeria. One research question was set while four hypotheses were tested at 0.05 level of significance. A sample of200students was selected using multistage sampling. A questionnaire was used to obtain relevant data which were analyzed using descriptive and inferential statistical tools. The main finding of the study was that the family has a strong influence on students' aspirations for entrepreneurial careers. The findings again indicated no significant difference in students' aspirations for entrepreneurial careers based on gender. However, significant differences were found on the bases of religion and course of study. Among the counseling implications was students should be taken into consideration in assisting students tomake appropriate career choices. It was recommended that school counselors should make available sufficient information on careers to students.